The Misdiagnosis of “Delusional Parasitosis” - Amin, Omar M. (Morgellon’s Disease and Neurocutaneous Syndrome (NCS): Cases and Recovery, 2021)
The body of knowledge on delusional parasites incriminates “delusional patients” as having imaginary external and internal symptoms that feel like parasite movements, dismisses them as psychiatric cases, and confuses cause with effect. We are critical of these arguments and believe that the symptoms of crawling and pin-pricking are genuine; just misinterpreted as parasite movements. Based on our research on over 1000 “delusional” patients since 1996 at our Parasitology Center, Inc. (PCI), we have established that the symptoms of crawling and pin-pricking are caused by toxicity from exposure to chemicals incompatible with host immune system, e.g., dental materials, that alter the propagation of normal nerve impulses. We have also observed that external parasites/organisms including springtails (Collembola), other arthropods, bacteria, and fungi represent only opportunistic infections of skin sites compromised by the toxicity disorder involving the elimination of toxins through the skin. We have described a new pathological disorder, Neuro- cutaneous Syndrome (NCS) to which justified “delusional parasitosis” and Morgellons disease cases could be assigned. We have developed a protocol for the resolution of the symptoms of NCS cases. When followed to the letter, all symptoms of NCS, conventionally called delusional parasites is, are invariably and irreversibly resolved.